2015
DOI: 10.1186/s13071-015-1099-4
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens vectored by the tick, Dermacentor reticulatus, in endemic regions and zones of expansion in Poland

Abstract: BackgroundDermacentor reticulatus plays an important role in the maintenance of pathogens of medical and veterinary importance in the environment. Currently two isolated populations of D. reticulatus are present in Poland –Western and Eastern. The range of the Eastern population covers endemic areas in eastern Poland but this population is expanding westwards creating an expansion zone in the centre of the country. The expansion zone in western Poland is occupied by the recently discovered Western population, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
89
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 77 publications
12
89
2
4
Order By: Relevance
“…and Rickettsia spp. Similarly, a coinfection value 2.8 times lower compared to the current study was reported Mierzejewska et al [30] who examined the Eastern and Western populations of the adult D. reticulatus ticks collected in Poland for the presence of 4 pathogens (Rickettsia spp., Babesia spp., B. burgdorferi s. l., TBEV), and found 3.0% of dual infections in the Eastern population (2.7% of R. raoultii with B. canis, and 0.3% of R. raoultii with TBEV), while in the Western population no such infections were found. The smaller value of co-infections reported also Ionita et al [54], who found that 5.3% of D. reticulatus ticks collected from dogs in Romania, were simultaneously infected with Rickettsia raoultii and Babesia canis.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…and Rickettsia spp. Similarly, a coinfection value 2.8 times lower compared to the current study was reported Mierzejewska et al [30] who examined the Eastern and Western populations of the adult D. reticulatus ticks collected in Poland for the presence of 4 pathogens (Rickettsia spp., Babesia spp., B. burgdorferi s. l., TBEV), and found 3.0% of dual infections in the Eastern population (2.7% of R. raoultii with B. canis, and 0.3% of R. raoultii with TBEV), while in the Western population no such infections were found. The smaller value of co-infections reported also Ionita et al [54], who found that 5.3% of D. reticulatus ticks collected from dogs in Romania, were simultaneously infected with Rickettsia raoultii and Babesia canis.…”
Section: Discussionmentioning
confidence: 50%
“…The role of this tick species in the transmission of some other pathogens in domestic animals and humans was also confirmed for Babesia caballi, Theileria equi, Anaplasma marginale, and Omsk haemorrhagic fever virus [18]. The role of D. reticulatus as a vector of other pathogens is less known, but seems probable with relevance to TBEV, and less probable with relevance to Francisella tularensis, Coxiella burnetii and Babesia microti [8,18,24,25,[29][30][31]35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…canis is an emerging pathogen in Europe (Solano-Gallego et al 2016) and, in the last decades, has become locally endemic in all countries bordering the Czech Republic. Canine babesiosis is present in localities with established populations of D. reticulatus in Germany (Naucke 2008), Austria (Halos et al 2014;Pantchev et al 2015), Poland (Mierzejewska et al 2015) and Slovakia (Kubelova (Beijing SBS Genetech, China). PCR products from the second run of nested piroplasmid PCR and from Hepatozoon PCR were purified (Gel/PCR DNA Fragment Extraction Kit, Geneaid Biotech, Taiwan) and subjected to sequencing using the amplification primers (Macrogen Europe, the Netherlands).…”
Section: Discussionmentioning
confidence: 99%
“…U psów stwierdzono dotychczas występowanie 6 gatunków, takich jak: Babesia canis, B. vogeli, B. rossi (określa-ne jako duże babeszje), B. gibsoni, B. conradae oraz B. vulpes (określane jako małe babeszje) (11,24). Obecnie wiadomo, że w Polsce endemicznie wystę-puje jedynie gatunek B. canis określany wcześniej jako B. canis canis (3,4,13,15,44). Pies, podobnie jak inne ssaki, u których występuje babeszjoza, jest żywicielem pośrednim tych pierwotniaków, natomiast żywicielem ostatecznym są kleszcze z rodziny Ixodidae.…”
Section: Artykuł Przeglądowy Reviewunclassified